The Effect of Carbon Monoxide Poisoning on Platelet Volume in Children - Halise Akça; Gizem Ürel; Can Demir Karacan; Nilden Tuygun; Emine Polat (Galenos Yayinevi, 2017)
Introduction: Carbon monoxide poisoning is one of the most important causes of morbidity and mortality. There is increasing evidence supporting the important role of mean platelet volume (MPV) as a marker of hypoxia and inflammation. In this study, we aimed to determine changes in MPV values in pediatric patients with carbon monoxide poisoning. Methods: We retrospectively evaluated children who were diagnosed with carbon monoxide poisoning in our hospital between January 2005 and 2014. Results: We included 228 children with carbon monoxide poisoning (49% male) in this retrospective, controlled study. The mean age of the patients was 88±56 months. Control group consisted of 200 age-matched healthy children. There was no statistically significant difference in MPV levels between the study and control groups (8.43±1.1 fL and 8.26±0.7 fL, respectively). No correlation of MPV and platelet count with carboxyhemoglobin (COHb) was found. Conclusion: In our study, it was determined that MPV value was not a helpful parameter for predicting the diagnosis of acute carbon monoxide poisoning in childhood. The difference between the MPV values and the lack of significance and the absence of correlation between MPV value and COHb level led to the fact that MPV was not a guide indicating the clinical severity of the condition.